Dexmedetomidine versus fentanyl in ultrasound-guided transversus Abdominis plane block for pain relief after elective cesarean delivery - Hesham Said Abdelraouf; Mohamed Abd-Allah Amin; Ahmed G Elsawy (Wolters Kluwer Medknow Publications, 2021)
Background Transversus abdominus plane (TAP) block is one of the multimodal techniques that are used to relieve postoperative pain in cesarean delivery. Addition of adjuvants to local anesthetic agents reduces postoperative opioid consumption and helps in prolonging their analgesic effect. Aim This study compared the influences of addition of dexmedetomidine versus fentanyl to bupivacaine in ultrasound-guided TAP block for postoperative analgesia after spinal anesthesia in cesarean delivery and evaluating the time to the first dose of analgesia postoperatively as the primary outcome. Patients and methods A total of 120 female patients scheduled for elective cesarean delivery were conducted in this study. Patients were divided into four equal groups. All patients received spinal anesthesia. Group TAP received ultrasound-guided TAP block using bupivacaine, group TAP-F received TAP block with addition of fentanyl to bupivacaine, group TAP-D received TAP block with addition of dexmedetomidine to bupivacaine, whereas control group received spinal anesthesia only, and morphine was used for pain relief. Postoperative, time to first dose of rescue analgesia, number of patients who requested rescue analgesia, patient satisfaction, and visual analog pain scale were recorded. Results The time to give rescue analgesic in TAP-D group was the longest in comparison with the other studied groups. Regarding the number of patients who requested rescue analgesia, at the end of 24 h, significant differences were observed between control group and the other groups, and least number of patients who requested rescue analgesia was in TAP-D group during 24 h postoperatively, and differences between this group and the other groups were highly significant. Conclusion Dexmedetomidine as an adjuvant to bupivacaine in TAP block delayed the time to first rescue analgesia when added to bupivacaine using ultrasound-guided technique and improved patients' satisfaction with decrease in total morphine consumption, whereas addition of fentanyl to bupivacaine has no added advantage.